Analysis of Village Income and Over Budget Calculation (SiLPA) Against Village Expenditures (Empirical Study of Villages in Katingan Regency 2016 - 2017 Period) - Efi Susanti; Tatik Zulaika; Oktobria Y. Asi (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2020)
The purpose of this study is to determine the effect of Village Income and SiLPA on Village Expenditure partially or simultaneously. Hypothesis testing in this study uses panel data regression analysis method with coefficient of determination test, f test, and t test. The results of this study indicate that the partial test results, Village Income has a significant positive effect. Simultaneous test results Village Income and Silpa together have a significant effect on Village Expenditure. In conclusion, from this coefficient is that the relative contribution given by the combination of Village Income and SiLPA variables to Village Expenditures is 100% while the remaining 0% is influenced by other variables not examined. While the partial test results show that Village Income has a significant positive effect on village expenditure and SiLPA has a significant negative effect on Village Expenditure.